Pretrial Failures in Ensuring the Merit of Cases: Critical Analysis and Innovative Reconstruction - Susilo , Erwin; Din , Mohd.; ., Suhaimi; Mansur, Teuku Muttaqin; Negara, Dharma Setiawan (Journal of Ecohumanism, 2024)
Determining a suspect has serious implications for human rights because it has the potential to limit human freedom through arrest and detention. However, the pre-trial mechanism which should function to test whether the suspect's determination is valid or not is often ineffective because it is formal administrative in nature, moreover strengthened by Article 2 paragraph (2) PERMA No. 4 of 2016. This research uses doctrinal legal research methods to analyze legal theories and norms governing pretrial and evidence. The aim of this research is to explain the legal basis for pretrial judges' authority to examine formal aspects, analyze the implications of their weaknesses, and determine the conceptualization of assessing material aspects in pretrial to overcome these weaknesses. This research found that the formal administrative approach was caused by the use of civil procedural law in pretrial as regulated in Article 101 of the Criminal Procedure Code and reaffirmed in Article 2 paragraphs (2) and (4) PERMA No. 4 of 2016, so that pre-trials tend to only seek formal truth and are unable to prevent prosecution based on inadequate evidence. Therefore, it is proposed to expand the authority of pre-trial judges so that they can examine the substance of the evidence used in determining a suspect, including ensuring that the determination of a suspect is not based on hearsay evidence, ensure that the determination of the suspect is not based on witnesses who cannot be sworn in, ensure that there is evidence that is decisive in determining the suspect, and ensure that the testimony of witnesses or suspects is obtained without pressure or violence. This reform is expected to strengthen the implementation of Article 28D of the 1945 Constitution and increase protection of human rights by ensuring that the determination of suspects is based on valid and reliable evidence.